Facile Surface Coatings for Performance Improvement of NMC811 Battery Cathode Material. Issue 2 (1st February 2022) - Sun, Xiao-Guang; Jafta, Charl J.; Tan, Susheng; Borisevich, Albina; Gupta, Ram B.; Paranthaman, Mariappan Parans
Abstract : High nickel content layered oxide LiNi0.8 Mn0.1 Co0.1 O2 (NMC811) is a promising cathode material with a high theoretical capacity of 200 mAh g −1 for use in high energy density lithium-ion batteries. However, its surface can easily get passivated by LiOH and Li2 CO3 due to its surface residual Li2 O being reacting with ambient moisture and CO2 . Herein, NMC811 was treated in a 3.0 M solution of lithium bis(fluorosulfonyl)imide (LiFSI) in dimethyl carbonate (DMC) at 60 °C for 8 h, 16 h and 24 h, respectively, resulting in coating of the NMC811 surface with LiF due to the basic nature of those residual lithium salts that react with LiFSI. The facile treatment of NMC811 in LiFSI/DMC not only improves the cycling stability but also enhances the capacity of the Li/NMC811 cells, mainly because of the thinning of the Li2 CO3 layer as suggested by cyclic voltammograms and impedance analyses. This method opens a new avenue for activation of passivated NMC811 particles for practical battery applications.